A versatile and modular modeling framework for diverse storage unit simulations. (August 2021) - Dicke, Paul; Resch, Simon; Steinbacher, Frank; Luther, Matthias; German, Reinhard
Abstract: Electrochemical batteries are becoming more essential for our increasingly renewable powered society every day. Therefore, the capability to simulate the behavior of these systems gains importance as well. Each storage unit from the broad technology spectrum comes with its own inherent characteristics and peculiarities proving it difficult to simulate various systems with one universal modeling approach. That however, is the most economical solution considering the effort-benefit ratio. In this work we therefore present and discuss a modular, highly versatile modeling methodology composed of several adapted submodels. The concept is able to simulate electrochemical storage units of diverging technologies as well as system size. Furthermore, it accounts for nonlinearities occurring due to current-voltage characteristics, current-rate as well as temperature dependencies, self-discharge, peripheral influence and aging phenomena. We outline benefits but also challenges of the approach and additionally showcase its sufficient fidelity, straightforward parametrization and versatility. Comprehensive simulation results are presented for a lithium-ion single cell as well as for four distinct storage systems of application relevant capacities, namely a lithium-ion rack, a valve-regulated lead-acid unit, an all-vanadium redox-flow battery and a high-temperature sodium-nickel-chloride system. Highlights: A highly versatile battery modeling framework of several submodels is presented. The concept is capable of addressing various nonlinear phenomena of battery behavior. The framework's modular design enables analyses in various levels of complexity. The Kinetic Battery Model is refined for a seamless integration into the framework. The framework is evaluated and validated for various battery types and system sizes.